Strong excess Faraday rotation on the inside of the Sagittarius spiral arm - Shanahan, Russell; Beuther, Henrik; Glover, Simon; Klessen, Ralf S.; Reißl, Stefan (The astrophysical journal. Part 2, Letters, 2019)
We present first results for Faraday rotation of compact polarized sources (1-2 GHz continuum) in The H i/OH/Recombination line (THOR) survey of the inner Galaxy. In the Galactic longitude range 39° 49°, RM drops off rapidly, while at ℓ 49°. We attribute the RM structure to the compressed diffuse warm ionized medium in the spiral arm, upstream of the major star formation regions. The Sagittarius arm acts as a significant Faraday screen inside the Galaxy. This has implications for models of the Galactic magnetic field and the expected amount of Faraday rotation of fast radio bursts from their host galaxies. We emphasize the importance of sensitivity to high Faraday depth in future polarization surveys.